PROMOTING RURAL TOURISM IN PERAK TENGAH DISTRICT THROUGH THE EXPANDING OF HERITAGE INTERPRETATION AND PRESENTATION - Harun, Siti Norlizaiha (PLANNING MALAYSIA, 2018)
The State of Perak is known for its richness and uniqueness in history and cultural heritage. However, the State’s tourism promotion has been focusing more on the popular destinations, leaving out those with heritage significance especially those located in the rural area. This is due to limited knowledge on method to interpret the cultural resources in the rural area, as well as unorganized interpretation programmes. This research has two aims, which are 1) to identify potential cultural heritage significance in Perak Tengah; and 2) to outline an interpretation plan of the potential cultural heritage as new tourist attraction of Perak. This research involves three stages; observation and inventory of resources, focus group interview and interpretation proposal. Results from the focus group discussion indicate the need to customize the interpretation and presentation of rural heritage especially on physical experience in community cultural activities. In the end, this study outlines interpretation guidance for heritage site operators on how visitors can experience the cultural heritage in the rural area.